Сравнительный анализ деятельности предприятий - Крылов Владимир Федорович (Финансы и статистика, 1981)
Экземпляры: КХ (20201210) / Инвентарный номер: 0255501 / Сис.шифр: 338С / Авт.знак: К 85 / ГРНТИ: 06 / ББК: 65